Laboratory Assessment of Recycled Concrete Waste for Improving Sandy Soils in Arid Regions - Fathia Alnaas; Samiha Abdelrahman (AlQalam Journal of Medical and Applied Sciences, 2025)
Although desert areas make up the majority of Libya’s land area, their use for urban development has been limited due to the challenging building conditions. A detailed study of the engineering characteristics of desert soils is necessary to allow for the sustainable utilization of this area. Although sandy soils have good load-bearing qualities, as the groundwater table rises to levels close to the foundation, their shear strength and overall stability may quickly decrease, requiring soil treatment before construction. One promising soil stabilization technique involves the utilization of recycled concrete waste (RCW), generated from the demolition of aging or damaged structures. Given the substantial increase in construction and demolition waste in Libya in recent years, incorporating such materials into geotechnical applications not only enhances soil performance but also contributes to environmental protection. This study presents a laboratory-based investigation into the influence of varying moisture content on the shear strength and its factors of natural sandy soil, as well as on soil treated with different percentages of (RCW) 0%, 3% and 6% of soil weight. Soil samples were collected from Kufra city in southeastern Libya. A comprehensive series of tests was conducted to determine the physical and mechanical properties of both untreated and treated soils. The results show that reusing construction waste as an efficient soil amendment significantly enhances the shear strength factors of sand at an addition ratio of 3% and 6% in both dry and wet cases, hence supporting sustainable construction practices in arid locations. Also, this addresses environmental issues and improves foundation performance.